The earliest attestation of laysa and the implications for its etymology - Al-Jallad, Ahmad (Proceedings of the Seminar for Arabian Studies, 2018)
This paper edits a Safaitic inscription containing the negator laysa, its earliest attestation in Arabic. Based on its form, I revisit the origins of laysa in Arabic as a whole and suggest a few possible scenarios to account for its source and shape.